Experiencing Shame: How Does Gender Affect the Interpersonal Dynamics of Restorative Justice?. (January 2022) - Scheuerman, Heather L.; Keith, Shelley
Although reintegrative shaming theory suggests that, in comparison to males, females are more interdependent and thus susceptible to reintegrative rather than disintegrative shaming, it is unclear how gender affects the type of shame experienced when considering interpersonal dynamics within restorative justice conferences. The involvement of the community within these conferences may affect how offenders are viewed, especially when considering the stigma female offenders experience for violating legal and gender norms. Using data from the Reintegrative Shaming Experiments, we find that interdependency conditions how gender affects the experience of shaming based on the type of others with whom offenders are interdependent.